Use of Information and Communication Technologies in a Resource-Constrained Setting: A Survey of Students from two Urban Universities in Azerbaijan - Chiragova, Vefa (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2024)
Information and communication technologies (ICT), or digital technologies, have become an integral part of higher education globally. The literature is dominated by studies from major industrialized countries where technology has been widely adopted in the education sphere. Using a survey constructed based on previous research, the present paper explores the rate and determinants of ICT use in a post-Soviet country with a considerable lag behind the Western education system. The survey, based on a convenience sample of 191 students from two urban universities in Azerbaijan, found that the most frequently used device is the mobile phone. While the majority of survey respondents accessed technology for free at their institution, only around half of the sample has had training on the use of technology resources. Nevertheless, the majority of students feel confident about using ICT, suggesting that they have developed the necessary skills through alternative methods, such as self-learning or peer support, even in the absence of formal training. Linear regression analysis suggests that the students’ ability to use ICT has a significant positive impact on their rate of ICT use.